Identity theft handbook : detection, prevention, and security - Biegelman, Martin T. (Hoboken, N.J. : Wiley, 2009)
The Handbook covers: the history and explosive growth of identity theft; Data breaches and the assault on privacy; Life and death consequences of medical identity theft; Case studies of criminals ignominiously admitted to the "Identity Theft Hall of Infamy"; Phishing, pharming, botnets, wireless, and P2P risk; Violent side of identity theft etc.
Includes bibliographical references and index.
rua 04/11/13
Loans
Keywords: Identity theft -- United States; Identity theft -- United States -- Prevention